AN ANALYSIS OF GRAMMATICAL ERRORS IN WRITING DESCRIPTIVE ESSAY MADE BY THE SECOND YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Devi Yenti; Fakhri Ras; Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The objectives of this research are to find empirical evidence of grammatical errors made by the second year students of English Study Program of Universitas Riau in writing descriptive essay and to find the sources that caused the errors. This is quantitative research with descriptive approach. Using cluster sampling, 25 students of class B were taken as the sample of this research. The data were collected throug writing test. The students were given blank papers contained a direction to write a descriptive essay with the topic “Describing Idol”. In analizing the data, several terminologies which deal with Error Analysis Technique were adopted such as identification, description, explanation, and evaluation of errors. Based on the process of identification and description, it was found that the students committed 498 errors that classified into four types of error which belong to Surface Strategy Taxonomy, they are: omission (25%), addition (22%), misformation (48%), and misordering (5%). Not only types of error to identify, this research also tried to explain the sources that caused the errors, which are: interlingual transfer (58%), intralingual transfer (33%), communication strategy (7%), and context of learning (2%). In addition, the errors made by the students were reconstructed into the correct form as the evaluation. Furthermore, in order to be good in using grammar in writing, several recommendations were given to the students such as doing more writing excercises and extensive reading, due to a complex productive skill which need more practice and more time to produce a good writing. In line with it, teachers need to provide interesting techniques with clearer explanation both in writing and grammar subjects and to follow up their writing to prevent the errors occur in the future.Key Words: Grammar, Error, Error Analysis, Writing, Descriptive Essay